Oromotor Dysfunction and Nutritional Status in Children with Cerebral Palsy: Implications for Inclusive Education - Marina Indriasari; Renan Prasta Jenie (Jurnal Konseling dan Pendidikan, 2025)
Children with cerebral palsy (CP) often experience oromotor dysfunction, affecting feeding processes and nutritional status. This condition may impair physical development, learning readiness, and participation in educational environments. This study analyzes the relationship between oromotor function and nutritional status in children and adolescents with CP and explores its implications for counseling services and inclusive education. A cross-sectional study was conducted with 44 children and adolescents aged 2–20 years with CP in Jakarta. Oromotor function was assessed through clinical evaluation of feeding difficulties, including chewing, swallowing, and oral motor control, categorized as normal or oromotor dysfunction. Nutritional status was assessed using WHO z-scores for BMI-for-age and height-for-age. Chi-square tests and Odds Ratios (OR) were used for statistical analysis. Findings revealed that 36.4% of participants experienced oromotor dysfunction, with 68.1% classified at GMFCS levels III–V. Children with oromotor dysfunction had a significantly higher proportion of abnormal nutritional status (p < 0.05), with nearly four times the risk (OR = 3.9; 95% CI: 1.1–13.8). This study is limited by its cross-sectional design and small sample size. These findings emphasize the importance of collaboration among healthcare professionals, educators, and counselors to support the development and educational success of children with CP.